The impacts of governance on environmental pollution in some countries of Middle East and sub-Saharan Africa: the evidence from panel quantile regression and causality - Bildirici, Melike (SPRINGER HEIDELBERG, 2022)
Governance is one of the basic determinants of pollution levels through property rights, the effective judicial system, etc. it is accepted as that bad governance because of inefficient regulatory structures, government bureaucracy, weak law enforcement, etc. support environmental pollution. In this context, in some countries of the Middle East and sub-Saharan Africa, it will be studied the impacts of governance on environmental pollution over the period of 1996-2018 by the panel quantile and Granger causality methods. The countries were selected by considering two different measurements, EPI (2020) index and governance index (2020). According to EPI (2020), these countries have low scores in terms of environmental quality, and in the governance index (2020), they have bad governance scores. In this study, in which panel quantile regression model is used, control variables are included in the model to prevent omitted-variable bias. The results of the analysis determined that the effect of governance on carbon emissions is positive, as well as that the effects of independent variables on CO2 emission are heterogeneous across quantities. Panel quantile regression revealed the evidence of the relation among the environmental pollution, two parameters of governance, FDI, financial development, human development index, and trade openness used as the explanatory variable and determined that government has the greatest positive effect on CO2 emission. On the other hand, by using traditional Granger causality and Dumitrescu-Hurlin causality methods, it was found the evidence of causality among governance and environmental pollution in the context of two parameters of governance. Accordingly, it was determined the evidence of unidirectional causality relation from political governance to environmental pollution and besides from economic governance to environmental pollution. And it was determined the evidence of unidirectional causality from FDI and the other explanatory variables to environmental pollution.
Keywords: Governance; Panel quantile regression; Panel causality test; environmental pollution; FOREIGN DIRECT-INVESTMENT; CARBON-DIOXIDE EMISSIONS; LAGRANGE MULTIPLIER TEST; INSTITUTIONAL QUALITY; ENERGY-CONSUMPTION; NATURAL-RESOURCES; RENEWABLE ENERGY; ERROR-CORRECTION; INFLOWS EVIDENCE; POLICY FORMATION; Environmental Sciences & Ecology